1994
DOI: 10.1007/bf01739921
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion of acyclovir is more effective than discontinuous infusion for treatment of genital herpes in an immunocompromised patient

Abstract: Recurrent genital herpes in immunocompromised patients may sometimes run a severe course spreading all over the perineum. Herpes simplex virus may develop resistance to acyclovir. A recurrent genital herpes simplex virus (HSV) infection complicating the treatment of Hodgkin's disease continued to spread in spite of acyclovir treatment via discontinuous infusion. Resolution of genital herpes was obtained with continuous infusion of acyclovir. Case ReportA 32-year-old woman had a history of recurrent genital her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…From a safety perspective, acyclovir plasma concentrations would need to remain below 50–70 mg/L, as these concentrations have been associated with neurotoxicity in a small subset of patients . Continuous‐infusion acyclovir has been effective in treating HSV after conventional intermittent acyclovir treatment failure . However, to our knowledge, the use and pharmacokinetics of continuous‐infusion acyclovir in the setting of concurrent extracorporeal life support (ECLS) and continuous renal replacement therapy (CRRT) have never been described.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From a safety perspective, acyclovir plasma concentrations would need to remain below 50–70 mg/L, as these concentrations have been associated with neurotoxicity in a small subset of patients . Continuous‐infusion acyclovir has been effective in treating HSV after conventional intermittent acyclovir treatment failure . However, to our knowledge, the use and pharmacokinetics of continuous‐infusion acyclovir in the setting of concurrent extracorporeal life support (ECLS) and continuous renal replacement therapy (CRRT) have never been described.…”
mentioning
confidence: 99%
“…[7][8][9][10] Continuous-infusion acyclovir has been effective in treating HSV after conventional intermittent acyclovir treatment failure. [11][12][13][14][15] However, to our knowledge, the use and pharmacokinetics of continuous-infusion acyclovir in the setting of concurrent extracorporeal life support (ECLS) and continuous renal replacement therapy (CRRT) have never been described. In this case report, we describe the pharmacokinetics of continuous-infusion acyclovir in a patient receiving concurrent ECLS and CRRT.…”
mentioning
confidence: 99%
“…We successfully eliminated herpes simplex virus-2 from the central nervous system in a patient with neonatal herpes simplex virus encephalitis using a continuous acyclovir infusion after conventional intermittent high-dose acyclovir and vidarabine failed. Some studies have reported on the effi cacy of continuous acyclovir infusion in herpes simplex virus, with or without acyclovir resistance, in immunodefi cient patients in whom intermittent acyclovir was not eff ective [1,4,7] . The diff erent effi cacies of these two therapies may be related to diff erent drug pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies in 16 immunosuppressed patients with Varicella-zoster virus or herpes simplex virus showed increased acyclovir penetration into the lesions with continuous infusion, resulting in vesicle fl uid levels near the plasma acyclovir levels [8] . As no reports exist on the serum and central concentrations of acyclovir suffi cient to eliminate herpes simplex virus in a case of herpes simplex virus encephalitis, we selected a dose of 2 mg / kg per hour, which is near the maximum reported safe and eff ective dose [1,4,7,8] . The therapy was eff ective clinically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation